PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM SDGs UNTUK MENDUKUNG PEMBANGUNAN BERKELANJUTAN DI DESA SIALANG PANJANG - Arfa Adha; Muhammad Rizki Rianda; Muhammad Afnan Nasrullah; Muhammad Zulkarnaen; Saibima Yusuf; Mawar Rizka; Istiqomah Khairunnisa; Beya Lillah Sakinah; Dinda Fitriyani; Nada Ramadhani; Anjhani Dwi Utari (Kampus Akademik Publiser, 2026)
This community service program was conducted in Sialang Panjang Village to support the achievement of several Sustainable Development Goals (SDGs) through community empowerment initiatives focusing on economic development, education, health, environmental management, and village infrastructure. The program aimed to enhance community capacity by improving digital marketing skills, promoting the utilization of medicinal plant gardens (Taman TOGA), increasing awareness of bullying prevention, strengthening youth leadership, encouraging environmental cleanliness, supporting village spatial information through simple mapping, and improving public health through stunting prevention education in collaboration with the local community health center (Puskesmas). The implementation employed a participatory approach involving observation, community needs assessment, socialization, training, demonstrations, mentoring, and collaborative activities with village stakeholders. The results indicated increased community participation and awareness in entrepreneurship, environmental conservation, public health, and educational development. The digital marketing training improved participants' understanding of online business promotion, while the establishment of the TOGA garden encouraged household medicinal plant cultivation. Educational activities enhanced students' awareness of anti-bullying values and leadership skills. In addition, the village clean-up movement, simple village mapping, and supporting infrastructure development, including the construction of a village gate, street name signs, and community exercise sessions, contributed to strengthening community engagement and supporting sustainable village development.